The Theory de La problematologie and hermeneutics: Towards an argumentative horizon to free interpretation from propositional tyranny - El Mouden El Mouden, Mohamed (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The problematic theory of the Belgian philosopher Michel Meyer opened a new philosophical and argumentative horizon to free human thought from the dominance of the propositional tendency. A tendency that imposed a systematic pattern, throughout the history of human thought, with a logical reference based on the principles of non-contradiction, identity and excluded third party. This article will focus on the contributions of the so-called “de la problematologie” theory to free interpretation from the propositional tyranny that reduces the plurality of answers to a propositional dichotomy A or -A .